IMPROVEMENT OF THE PROCESS OF NEW BUSINESS OF SHIP BUILDING INDUSTRY - Minto Basuki; Djauhar Manfaat; Setyo Nugroho; AAB Dinariyana (Universitas Hayam Wuruk Perbanas, 2012)
Shipbuilding industry is an industry group which has high risk. For that reason, the managementshould include risk assessment. The production process of new buildings in theshipbuilding industry is grouped into three major parts, namely the work of design, materialprocurement and production processes. Each stage of the production process will bring therisk and will accumulate on the overall risk. If the risk is not anticipated, the possibility ofdelays in the production process will be even greater. Risk assessment performed on eachproduction process by using a probabilistic approach to the principle of multiplication in thetheory of opportunity. Risk analysis performed on the construction of fast patrol boats was inthe construction number 268, 269 and 270 on the PT. PAL Indonesia. From the analysis, itwas obtained the greatest probability of occurrence of sequential delay which is in the processof the material, the production, and design group. The potential for loss is due to the riskof unanticipated costs due to factors affected by delays in production processes. Performancefactors are still required for further study.